ANALISIS TINGKAT PENGETAHUAN PEMILIH PEMULA TERHADAP PELAKSANAAN PEMILU TAHUN 2019-2024 DI DESA MUARA LANGSAT KECAMATAN SENTAJO RAYA - Rahmadillah, Wulan; Erlinda, Sri; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This research is motivated by the fact that novice voters still lack knowledge and understanding of the election implementation process so that they do not give their voting rights in general elections, novice voters are easily influenced by certain interests, especially by their closest people, such as family members ranging from parents to relatives. and the lack of interest of novice voters to follow the explanations given by the General Election Commission as the organizer to stimulate the awareness of new voters. The formulation of the problem in this study is how the Level of Knowledge of Beginner Voters on the Implementation of the 2019-2024 Election in Muara Langsat Village, Sentajo Raya DistricT. This study aims to determine the Level of Knowledge of Beginner Voters on the Implementation of the 2019-2024 Election in Muara Langsat Village, Sentajo Raya District. This research was conducted from September 2019 to January 2020. The sampling technique was the simple random sampling technique. The sample in this study amounted to 100 people. Data collection techniques used are in the form of observation techniques, questionnaires (questionnaires), interviews and documentation. In analyzing the data, researchers used quantitative descriptive methods. The results of this study indicate that the percentage of respondents who answered Very Know + Know was 46.49% in which the Poor category was in the range of 25.01% - 50.00%. It can be concluded that the Knowledge of Beginner Voters in the Election in Muara Langsat Village, Sentajo Raya District, the role is at the